Media Restrictions as the Image Formation Tool: the Case Study of Singapore’s Prime Minister Lee Kuan Yew Popularity - Juodytė, Aurelija; Colin, Ng Zhen Xiang (Žurnalistikos tyrimai, 2015)
We live in the world full of nice people. The media make us think so as we are surrounded by the images of sport, pop culture, fashion industry, entertainment media, and business leaders. We face them even in the news programs and the press. Of course, the photos and other visual outlets of politicians join the general publicity of personality cult. How do these people appear in the journalist media? Why are they exposed in a positive manner while the crucial role of journalism’s “watchdog” function is to demonstrate weaknesses in order to get them into political agenda and improve? We live in the world where there is a huge business of personality promotion and selling beneath the media, and this business is called celebrity branding and news management. The media skip it from exposure. Journalism too, but why? Who is in charge that people in the media become celebrities? Who, the source or the media, is related to the fact that their audience becomes attached to the celebrities and is involved into a never-ending follow-up communication with them? These questions arise when we focus on journalism’s role in the public opinion formation process in general and image management in particular. The issue may be approached by various ways, but the present article narrows the scope of analyses mainly to the issue of political environment impact on the image of the political actor. Such a choice is made due on the factor that political environment covers both the macro (institutional) and micro (content) levels of restrictions the traditional media encounter, and due to the reason that the scope of mediated politics enables the holistic view of the media field professionals (public relations practitioners, sources, and journalists) performance and its influence on the final product. The disclosure of how the personality campaign is organised in order to reach a wide coverage and depict a positive image is of cognitive value also because the case study is made with the Singapore Prime Minister’s example – the international aspect introduces the global patterns of the celebrity phenomenon and also allows to discuss the media regulation in Singapore. First of all, the present article introduces the theoretical background for the case study, then it examines the state of the media in Singapore, showing the ownership specifics, regulation peculiarities and free speech constraints arising from regulation rather than from professionalism. The psychologically fair factor is disclosed through the analysis of legal acts, especially the Internal Security Act. The spiral of silence theory explains the supporters of such political environment that enables a long-lasting positive attitude towards the Singapore Prime Minister Lee Kuan Yew and explains his popularity and a successful image-making job.